Global shocks alert and monetary policy responses - Olatunji Abdul Shobande; Oladimeji Tomiwa Shodipe; Simplice Asongu (African Governance and Development Institute (AGDI), 2019)
The study examines the role of global predictors on national monetary policy formation for Kenya and Ghana within the New Keynesian DSGE framework. We developed and automatically calibrated our DSGE model using the Bayesian estimator, which made our model robust to rigorous stochastic number of subjective choices. Our simulation result indicates that global factors account for the inability of national Central Banks to predict the behaviour of macroeconomic and financial variables among these developing nations.
Keywords: E32; 62; 330; Business Cycle; Macroeconomic policy; Financial crises